Amoxicillin for acute lower respiratory tract infection in primary care: subgroup analysis by bacterial and viral etiology. - Bruyndonckx, R; Stuart, B; Little, P; Hens, N; Ieven, M; Butler, C; Verheij, T; Goossens, H; Coenen, S (Elsevier, 2017)
Objective We aimed to assess the effects of amoxicillin treatment in adult patients presenting to primary care with a lower respiratory tract infection (LRTI) who are infected with a potential bacterial, viral, or mixed bacterial/viral infection. Methods The multicenter randomized controlled trial focused on adults with LRTI not suspected for pneumonia. Patients were randomized to receive either antibiotic (amoxicillin 1g) or placebo three times daily for seven consecutive days using computer-generated random numbers (follow-up 28 days). In this secondary analysis of the trial, symptom duration (primary outcome), symptom severity (scored 0-6), and illness deterioration (reconsultation with new or worsening symptoms, or hospital admission) were analyzed in pre-specified subgroups using regression models. Subgroups of interest were patients with a (strictly) bacterial, (strictly) viral or combined infection and patients with elevated values of procalcitonin, C-reactive protein or blood urea nitrogen. Results 2058 patients (amoxicillin n=1036; placebo n=1022) were randomized. Treatment did not affect symptom duration (n=1793). Patients from whom a bacterial pathogen only was isolated (n = 207) benefited from amoxicillin in that symptom severity (n= 804) was reduced by 0.26 points (95% CI: [-0.48; -0.03]). The odds of illness deterioration (n=2024) was 0.24 (95% CI: [0.11; 0.53]) times lower from treatment with amoxicillin when both a bacterial and a viral pathogen were isolated (combined infection; n=198). Conclusions Amoxicillin may reduce the risk of illness deterioration in patients with a combined bacterial and viral infection. We found no clinically meaningful benefit form amoxicillin treatment in other subgroups.